2004
DOI: 10.1016/j.physb.2004.03.247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the lattice thermal conductivity of Kr/Ar superlattice nanowires

Abstract: The nonequilibrium molecular dynamics (NEMD) method has been used to calculate the lattice thermal conductivities of Ar and Kr/Ar nanostructures in order to study the effects of interface scattering, boundary scattering, and elastic strain on lattice thermal conductivity. Results show that interface scattering poses significant resistance to phonon transport in superlattices and superlattice nanowires. The thermal conductivity of the Kr/Ar superlattice nanowire is only about 1/3 of that for pure Ar nanowires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 33 publications
3
73
1
Order By: Relevance
“…The similar periodic length dependent thermal conductivity was also observed in Kr/Ar superlattice NWs. 78 In addition to the random and interface scatterings of phonon, the surface scattering is another way to reduce thermal conductivity. It has been demonstrated that thermal conductivity of NWs can be reduced further obviously by introducing more surface scattering: making SiNWs hollow to create inner surface, i.e.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…The similar periodic length dependent thermal conductivity was also observed in Kr/Ar superlattice NWs. 78 In addition to the random and interface scatterings of phonon, the surface scattering is another way to reduce thermal conductivity. It has been demonstrated that thermal conductivity of NWs can be reduced further obviously by introducing more surface scattering: making SiNWs hollow to create inner surface, i.e.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…In the past two decades, molecular dynamics (MD) simulations have been employed extensively to study the interface thermal conductance across various material interfaces, [5][6][7][8][9][10][11][12][13] such as Kr/Ar, 7 Si/In, 11 carbon nanotube/Si, 12 Si/polymer 9 and PbTe/GeTe. 13 A relatively good understanding of the reduced lattice thermal conductivity in nanostructured materials due to the thermal boundary resistance has been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…魏 l can be calculated by multiplying the interface thermal conductance G by d, G = t蠀C 4 , t is the interfacial phonon transmission coefficient, and 蠀 and C the average phonon velocity and the specific heat of two phases, respectively [19]. Therefore,…”
mentioning
confidence: 99%